Struktur Komunitas Bivalvia di Pantai Desa Bonebobakal Kecamatan Lamala Kabupaten Banggai - Gusti Wardana Karsono; Firga Nabila Lige; Alwia Samaduri (Jurnal Biologi Babasal, 2023)
Bonebobakal Village is one of the villages in Banggai Regency, Central Sulawesi. Bonebobakal Village Beach is characterized by a rocky coastal ecosystem, which has a variety of coral flora and fauna communities. Various types of communities of invertebrate biota organisms are found in Bonebobakal Village Beach, one of which is Bivalvia. The purpose of this study was to determine the condition and types of Bivalves found on the beach of Bonebobakal Village. The research method used is descriptive quantitative with cruising survey method on plot line transect. The results showed that there are several types of Bivalves on the beach of Bonebobakal Village such as Anadara granosa (pigeon clam), Perna viridis (green clam), Pinctada sp. (pearl clam) and Hippopus hippopus (clam). Based on the value of data analysis from both stations, the value of the diversity index (H') is 1.2023 classified as moderate, while the uniformity index (E) is 0.8673 classified as stable. The dominance index (D) is 0.3473 classified as low, and the density index in a row from the highest to the lowest is Anadara granosa species (50.49%), Hippopus hippopus (23.30%), Perna viridis (17.48) and finally Pinctada sp. (8.74%).